Influence of recycled flow operation on the value of minimum energy consumption - S. L. Nazanskiy; A. V. Solokhin; O. Yu. Istomina (Тонкие химические технологии, 2011)
The influence of recycled flow operation on the value of minimum energy consumption for total conversion of A reagent to B product was studied with A↔B reaction as an example.